Implementation Of Integrated Quality Management Academic Supervision Of School Principles In Improving The Quality Of High School Teachers Professional Competence - Mulyadi, Dedi; Wasliman, Iim; Hanafiah; Sauri, R. Supyan (Lafadz Jaya Publisher, 2022)
This research is motivated by the limited ability of principals in developing teacher abilities, less effective leadership styles and the implementation of academic supervision. This research is a qualitative research with case study method. The results of this study indicate that planning for academic supervision has become a principal program and the preparation of this plan has involved all parties in the school. The principal performs academic supervision of all teachers, in which the principal is assisted by the vice principal and senior teachers who are given a letter of assignment. Supervision of academic supervision, the principal checks and signs the teacher's administrative documents and monitors when the teacher conducts teaching and learning activities in the classroom. Follow up on the results of academic supervision by providing input both orally and in writing. Problems, among others, some teachers in the implementation of supervision are not according to a predetermined schedule, and senior teachers are less well versed in IT. Academic supervision solutions include adjusting the schedule in academic supervision in accordance with the teacher's readiness, and mentoring senior teachers who do not understand IT.